Literary Stylistics Features in the Musical Drama NURBAYA by Indonesia Kaya - Haris, Muhammad Abdul; Meisuri, Meisuri; Pulungan, Anni Holila (Jurnal Bahasa dan Sastra, 2024)
This study examines the literary stylistic features in NURBAYA, a contemporary Indonesian musical drama produced by Indonesia Kaya. Employing Leech and Short's (1981) framework, the research focuses on sound patterns and figures of speech, investigating how these elements enhance narrative cohesion and emotional impact while reflecting cultural values. Using qualitative content analysis, the study systematically categorizes and interprets stylistic features in conversation utterances and song lyrics. The analysis reveals a prevalence of sound patterns, particularly rhyme, which contributes to the musical's rhythmic quality and cohesion. Figures of speech, notably litotes, are employed to reflect cultural values of politeness and subtlety. For instance, the frequent use of litotes (found in 35% of character dialogues) underscores adherence to traditional norms, enhancing the play's cultural resonance. NURBAYA, as a bridge between traditional and contemporary Indonesian theatre, offers a unique lens for examining the evolution of literary style in performance art. This study demonstrates how specific literary devices enrich artistic expression and reinforce cultural themes in contemporary Indonesian theatre. These findings contribute to our understanding of the interplay between linguistics, literature, and cultural expression in performing arts, offering insights into how stylistic analysis can illuminate broader sociocultural dynamics in theatrical works.